Developing a winning sport team culture: organizational culture in theory and practice. Issue 8 (3rd August 2018) - Cole, Jason; Martin, Andrew J.
Abstract: This case study reviews strategies for identifying, establishing and influencing sport team culture and leadership, based on Edgar Schein's three-level theoretical model of organizational culture integrating artefacts, values and beliefs and core assumptions. Specifically, we examine the success of a professional rugby team in New Zealand, the 2014 ITM Cup champions, the Manawatu Turbos. Semi-structured interviews were conducted with past and present coaches ( N = 3) and captains ( N = 3). Key findings include the need to formally recognize culture, including establishing and reinforcing values, as a tangible element of sport team management practice. A flat organization structure has helped facilitate a suitable environment for collective leadership to flourish. Implications for sport and business teams are the need to acknowledge culture as a core component, and conduct a culture audit to establish the current and desired culture through an aligned combination of informal and formal transformational leadership.